Management of mandibular fractures with ESF type-I, bone plating, and interfragmentary wiring in cattle - Patwa, Ruchi; Bishnoi, A.K.; Bishnoi, P.; Kumari, Ankita; Diwedi, Shivangi (Indian Journal of Veterinary Surgery, 2026)
Three cattle of different ages were reported with history of injury due to accidents leading to mandibular fractures. All fractures were involving horizontal ramus of the mandible, of which two were bilateral (C1 and C2) and one was unilateral (C3). In C1, bilateral hemimandibular fracture was stabilized with type-I ESF, and in C2, only the displaced left hemimandible fracture was stabilized with Limited Contact Dynamic Compression Plate (3.5, 6-hole LC-DCP). Unilateral left hemimandibular fracture in C3 was stabilized with inter-fragmentary orthopaedic wiring. In all the three cases, postoperative antibiotics, analgesics, multivitamins and calcium-phosphorus supplement were prescribed, also, regular flushing of oral cavity with light potassium permanganate solution, along with flushing of ESF pin tract in C1. Owners were advised to provide soft feed to animals for 6 weeks postoperatively. In the final outcome, all the three animals were able to use the jaw for feed mastication.